Avaliação histomorfométrica da osseointegração de implantes em pacientes com alterações metabológicas - Pinheiro, Felipe Pimentel (2019)
The increase of patients with metabolic syndrome in the dental clinic and the lack of studies in implantolody in the subject for information about implants osseointegration in metabolically compromised patients. The present study aims to evalvate histopathological osseointegration of dental implants in those indivuduals, answering the question whether the amount of bone tissue formed around dental implants are similar between patiens with or without metabolic syndrome. Twenty patients were selected for this research, and they were divided in two groups, control group (n = 12) and test group (n = 8). Four implants, Unitite® model were installed per patient, in the edentulous mandible between mental foramens, totaling 80 implants. Besides that, at the same surgical time, a prototype of implants was installed in each patient with the same surface treatment and implant design characteristics used. After a period of sixty days, at the second surgical time, the prototype was removed to be analyzed regarding which was determined by magnification and a specific sofware. Significant differences were found by Student test t at significance level of 5%. Current showead no differences in the amount of formed bone around implants betweewn groups.